Correlation Between Body Fat Composition and Blood Pressure Level Among Medical Students in a Tertiary Care Teaching Hospital In Pokhara, Nepal - Tiwari, Indu; Bhattarai , Anshu; Karmacharya , Poonam; Gurung, Preetu (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Increase in body fat is a common finding in young adults due to sedentary lifestyle and unhealthy dietary habits predisposing an individual to increase in blood pressure which is a common cause of cardiovascular morbidity and mortality. This study aimed to determine the association between body fat composition and BP level in young adults. Methods A cross sectional study was conducted among 350 students of Manipal College of Medical Sciences from January to June, 2020. A structured proforma was used to collect the required information about the subjects and measurement of height, weight, waist and hip circumference, BP was done following standard methods. Body fat percentage was assessed by skinfold thickness. Results The prevalence of were overweight and obesity was found to be 35.14%. Systolic, diastolic and combined hypertension was found in 64.7%, 53.26% and 57.64% respectively, in overweight and obese population. Increase in body fat percentage in boys and increase in waist hip ratio in girls showed no correlation with increase in systolic, diastolic and mean arterial pressure. However, increase in BMI was strongly correlated (p<0.05) with increase in all the measures of blood pressure- systolic, diastolic and mean arterial pressure. Conclusions Body mass index is a better predictor of increased blood pressure level than body fat percentage and waist hip ratio.